Pembinaan Optimalisasi Peran Perempuan Desa dalam Literasi Inovasi Digital Marketing Guna Menjaga Keberlangsungan Usaha di Desa Kelungkung - Zulkieflimansyah Zulkieflimansyah; Hasrul Sani; Lesnawati Lesnawati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The main purpose of this community empowerment activity is to provide guidance on optimising the role of village women in digital marketing innovation literacy to maintain business sustainability in Kelungkung Village. The methods used in this community service activity are tutorial methods, mentoring methods, discussion methods and evaluation. The results achieved from this activity are: (1) The enthusiasm of the PKK of Kelungkung Village for digital marketing innovation literacy activities with various conditions of limited time and age, (2) Can understand and practice how to create a market place account to do online marketing, (3) Can understand material about online marketing strategies, (4) Able to plan a digital marketing business, (5) Able to compile small business performance evaluation management.